TIO2 Nanoparticles Reinforced Lead-Free 96.5Sn–3.0Ag–0.5Cu Solder Paste for Ultra-Fine Package Assembly in Reflow Soldering Process - Che Ani, F.; Jalar, A.; Ismail, R.; Mustafa, Z.; Saad, A.A.; Khor, C.Y.; Othman, N. K.; Tura Ali, M.Y.; Fatah, M.A.; Mukhtar, M.; Abas, A. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Ultra-fine package assembly using TiO2 nanoparticle reinforced lead-free solder paste was carried out in the reflow soldering process. TiO2 nanoparticles were mixed with the SAC solder paste at 0.01, 0.05 and 0.15 wt.%. The ultra-fine package (passive capacitor) was mounted on PCB with a thickness of 2.0 mm using the nanocomposite solders. Voids, microstructure and TiO2 nanoparticle distributions were inspected through the X-ray, SEM and HRTEM. The ultra-fine solder joints were formed perfectly without any void formation. The TiO2 nanoparticles are distributed homogenously in the solder joint. The mechanism of IMC reaction during the reflow soldering process is also discussed. Homogeneous mixing of nanoparticle plays a significant role for the distribution of the nanoparticle in the solder joint.